2020
DOI: 10.1002/jsde.12412
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Approaches on the Synergistic Interaction between Double‐Headed Anionic Amino Acid‐Based Surfactants and Hexadecyltrimethylammonium Bromide

Abstract: Theoretical investigations on the micellization of mixtures of (i) amino acid‐based anionic surfactants [AAS: N‐dodecyl derivatives of aminomalonate, −aspartate, and ‐glutamate] and (ii) hexadecyltrimethylammonium bromide (HTAB), were carried out at different mole ratios. Variation in the theoretical values of critical micelle concentration (CMC), mole fraction of surfactants in the micellar phase (X), at the interface (Xσ), interaction parameters at the bulk/interface (βR/βσ), ideality/nonideality of the mixi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 70 publications
0
4
0
Order By: Relevance
“…Here, X R 1 represents the micellar mole fraction of the drug CPZ in the mixed system of drug-zwitterionic surfactants; cmc 1 is the cmc of the drug CPZ and cmc 2 is the cmc of zwitterionic surfactants (C 12 DmCB and C 14 Ab). Eqn (15) was solved by an iterative process to obtain X R 1 values. These X R 1 values were used to calculate the interaction parameter (b R ).…”
Section: Packing Parametermentioning
confidence: 99%
See 1 more Smart Citation
“…Here, X R 1 represents the micellar mole fraction of the drug CPZ in the mixed system of drug-zwitterionic surfactants; cmc 1 is the cmc of the drug CPZ and cmc 2 is the cmc of zwitterionic surfactants (C 12 DmCB and C 14 Ab). Eqn (15) was solved by an iterative process to obtain X R 1 values. These X R 1 values were used to calculate the interaction parameter (b R ).…”
Section: Packing Parametermentioning
confidence: 99%
“…8,9 The critical amphiphile concentration mandatory for the commencement of the formation of an aggregated assembly, referred generally to as a micelle, is called the critical micellar concentration (cmc). 10,11 Mixed micellar systems can consist of two or more types of amphiphiles available in the literature [5][6][7][12][13][14][15][16] and belong to any combination of anionic, cationic, nonionic, and zwitterionic surfactants. Mixed surfactant systems almost always show an improvement in interfacial properties (e.g., lower cmc, greater surface activity, etc.)…”
Section: Introductionmentioning
confidence: 99%
“…Dicationic histidine derivatives were documented as promising agents for antibacterial treatment against new generations of microorganisms like methicillin-resistant Staphylococcus aureus [ 47 ]. The authors of [ 48 ] investigated the surface-active and micelle-forming properties of three anionic dicarboxylic amino acid-based surfactants in combination with the cationic compound cethyltrimethylammonium bromide (CTAB). It was shown that maximum number of the cationic surfactant CTAB molecules on the micellar surface leads to the formation of close-packed micellar structures [ 49 ].…”
Section: Self-assembly Of Amphiphilic Compoundsmentioning
confidence: 99%
“…Kang et al studied The surface properties and the microaggregates of a sulfonate gemini surfactant 1,2‐bis( N ‐dodecyl‐ N ‐propane sulfonate sodium)‐ethane (SGS12) and conventional cationic surfactant CTAB mixtures (Kang et al, 2020). Barai et al explored theoretical approaches to the synergistic interaction between hexadecyltrimethylammonium bromide (HTAB) and double‐headed anionic amino acid‐based surfactants (Barai et al, 2020). Ren et al probed the interaction behavior between an amphoteric sodium N ‐acyl amino sulfonate based on castor oil (AAS‐CO) and the cationic stearyltrimethyl ammonium bromide (STAB) (Li et al, 2021).…”
Section: Introductionmentioning
confidence: 99%